Returns to schooling in urban China from instrumental variable (IV) estimation - Lim, Bing Wey (2015)
This paper discusses the importance of instrumental variables in achieving a more accurate estimate of returns to schooling in urban China. In particular, we have identified an interaction of first-born and sibling composition, with age, as the instrument set in our estimation of returns to schooling in urban China. The findings indicate that the returns to schooling for male urban workers to be approximately 9.1%. This is a progress that China has made, in terms of accumulating higher human capital, as compared to that before the reform. This paper also challenges the validity of the instrument set chosen. In view of this, the results of the instrumental variable regression imply that the instrument set we have chosen is strong and valid.